IUTAM Symposium on Mechanics and Reliability of Actuating Materials proceedings of the IUTAM Symposium held in Beijing, China, 1-3 September, 2004 - IUTAM Symposium on Mechanics and Reliability of Actuating Materials (Solid mechanics and its applications,, 2006)
Actuating materials hold a promise for fast-spreading applications in smart structures and active control systems, and have attracted extensive attention from scientists of both mechanics and materials sciences communities. High performance and stability of actuating materials and structures play a decisive role in their successive applications as sensors and actuators in structural control and robotics. The advances of actuating materials, however, recently encountered a severe reliability issue. For a better understanding toward this issue, scientific efforts are of paramount significance to gain a deep insight into the intricate deformation and failure behaviors of actuating materials. To examine the state of the art in this subject, the general assembly of IUTAM approved in August, 2002 at Cambridge University, UK, a proposal to hold an IUTAM symposium to summarize the relevant research findings. The main themes of the symposium are: (i) the constitutive relations of actuating materials that couple mechanical, electrical, thermal and magnetic properties, as well as incorporate phase transformation and domain switch; (ii) the physical mechanisms of deformation, damage, and fatigue crack growth of actuating materials; (iii) the development of failure-resilient approaches that base on the macro-, meso-, and micro-mechanics analyses; (iv) the investigation of microstructural evolution, stability of phase transformation, and size effects of ferroelectric ceramics, shape memory alloys, actuating polymers, and bio-actuating materials. The above problems represent an exciting challenge and form a research thrust of both materials science and solid mechanics. The IUTAM Symposium (GA.